Pregnancy and Neonatal Outcomes With Levothyroxine Treatment in Women With Subclinical Hypothyroidism Based on New Diagnostic Criteria: A Systematic Review and Meta-Analysis - Ding, Zheng; Liu, Yindi; Maraka, Spyridoula; Abdelouahab, Nadia; Huang, He-Feng; Fraser, William D.; Fan, Jianxia (Frontiers in Endocrinology, 2021)
Background: Subclinical hypothyroidism (SCH) during pregnancy has been associated with multiple adverse maternal and neonatal outcomes. However, the potential benefits of levothyroxine (LT4) supplementation remain controversial. Variations across studies in diagnostic criteria for SCH may, in part, explain the divergent findings on the subject. This study aimed to assess the effect of LT4 treatment on pregnancy and neonatal outcomes among pregnant women who were diagnosed as SCH based on the most recent diagnostic criteria. Methods: We conducted a systematic review and meta-analysis of the literature published from inception to January 2020. The search strategy targeted the studies on pregnancy and neonatal outcomes following LT4 treatment in women with SCH based on 2017 American Thyroid Association diagnostic criteria. Pooled effect sizes were estimated using fixed and random effect models, according to the absence or presence of heterogeneity which was assessed using the I-squared statistic. Sources of heterogeneity and the stability of results were evaluated through sensitivity analysis. Results: Of the 2781 identified references, 306 full-text articles were screened for eligibility. Finally, 6 studies including a total of 7955 participants were retained for analysis. Summary effect estimates indicated that pregnant women with SCH treated with LT4 had a lower risk of pregnancy loss [odds ratio (OR) = 0.55, 95% confidence interval (CI): 0.43-0.71], preterm birth (OR=0.63, 95% CI: 0.41-0.98) and gestational hypertension (OR = 0.78, 95% CI: 0.63-0.97) than those in control group. Conclusion: LT4 treatment in pregnant women with SCH may reduce the risk of pregnancy loss, preterm delivery and gestational hypertension.